A Platform for the Implementation of Adaptive On-line Courses: Description and Teachers' Point of View - Julián Moreno Cadavid; Demetrio Arturo Ovalle Carranza; Rosa María Vicari (Universidad Autónoma de Baja California, 2014)
Adaptation is a desirable feature in on-line courses which allows for the consideration of students particular characteristics and needs. However, it is not common for teachers to embrace technologies related to this feature. This phenomenon may be mainly attributed to: a) unawareness of appropriate authoring tools, and/or b) resistance to their use. Regarding this panorama, this research has two purposes. The first purpose is to present a web platform to create adaptive on-line courses that considers three adaptive functionalities: curriculum sequencing, content presentation and assessment. The second purpose is to present a validation for such platform with real users, more specifically, 51 teachers of K-12. The obtained results show that even if there was general distrust while using the platform, there was also a overall interest in rely on a tool that grants teachers in providing an individualized learning experience.